Safety, tolerability, pharmacokinetics, and pharmacodynamics of a TLR7 agonist prodrug RO6870868 in healthy volunteers - Joseph F. Grippo; Ilia Folitar; Sharon Passe; Qiudi Jiang; Ignacio Rodriguez; Scott H. Fettner; Elizabeth Calleja (Wiley, 2021)
Abstract RO6870868 is an oral prodrug of the toll‐like receptor 7 (TLR7) specific agonist, RO6871765. TLR7 agonists augment host immune activity and are in development to treat hepatitis B infection. We evaluated the safety, tolerability, pharmacokinetics (PKs), and pharmacodynamics (PDs) of RO6870868 in a first‐in‐human, phase I, randomized, single ascending oral dose study in 60 healthy volunteers at 6 dose levels (200-2000 mg). Single oral doses were generally well‐tolerated with a predictable safety profile associated with dose‐dependent increases in systemic interferon. No serious adverse events (AEs) were reported and no subject withdrew from the study due to an AE. No clinically significant changes were observed in vital signs, electrocardiograms, or laboratory parameters. Following oral RO6870868 doses, plasma RO6871765 concentrations increased rapidly, exhibiting mean terminal half‐life ranging 2-6 h across all cohorts, with area under the plasma concentration versus time curve extrapolated to infinity (AUC0‐∞) increasing proportionally with dose. A pattern of dose and time‐dependent PD activity was demonstrated consistent with engagement of the TLR7 system. Single RO6870868 doses activated components of the TLR innate immune system in a dose‐dependent manner with adequate safety and tolerability. Single‐dose data in healthy volunteers are useful to evaluate safety, PK, and PD activity of TLR7 agonists and help to guide dose and regimen selection for further trials in patients with chronic hepatitis B.